Determinant of Age at First Birth in Nepal: A Study of Adolescent and Youth Women in NDHS 2016 - Khanal, Prabha (Journal of Population and Development, 2021)
First birth is one of the most significant events in woman’s life which signifies her taking on the roles and responsibilities of a mother. This article tries to figure out the factors that determine the age at first birth of women aged 15 to 24 years. Utilizing the Nepal Demographic and Health Survey 2016 data, this study examines the socio economic and demographic determinants of age at first birth among the women aged 15-24 years with the 4,849 married women. The analysis has made using the mean distribution and two tailed Pearson’s correlation has been used for statistical test. The result shows that women’s education, occupation, wealth index and age at marriage has positive correlation with the age at first birth. It is expected that higher the use of contraceptive method has lower the fertility. Though, use of contraceptive methods seems no any association with the age of women at first birth. Study reveals that unmet need for family planning is high of that age group. That’s why, supply of family planning methods of target population group can play vital role to postpone age at first birth.